Evaluation of High Fibers Okara and Soybean Bran as Functional Supplements for Mice with Experimentally Induced Type 2 Diabetes - Ismaiel Manal; Yang Hong; Cui Min (Polish Journal of Food and Nutrition Sciences)
The objective of this study was to evaluate and compare the anti–diabetic efficacy of feeding diets supplemented with okara and soybean bran to ICR mice with experimentally–induced type 2 diabetes. While okara and soybean bran are from the same source, there is no performed research comparing the effects of these soybean byproducts on glycemic status. Normal and streptozotocin–induced type 2 diabetic ICR mice were assigned either to a normal diet in the normal control group, a high fat diet only in the diabetic control group, a high fat diet supplemented with 15% okara in the okara group, a high fat diet supplemented with 15% soybean bran in the soybean bran group or a high–fat diet supplemented with 0.1% metformin in the metformin group for 8 weeks. The biochemical parameters, the organs relative weights and liver histological structure of mice were determined. Okara was significantly effective in controlling hyperglycemia and improving glucose tolerance. Moreover, the antihyperglycemic effect of okara was broadly comparable with the actions of metformin. Feeding okara and soybean bran caused hypolipidemic effects. In addition, they had a strong cytoprotective effect on hepatocytes. Soybean bran seemed more efficient than okara in alleviating hepatic cell histological changes. Results demonstrated the potential benefit of okara and soybean bran in glycemic control and reducing the risk of type 2 diabetes complications.